2019
DOI: 10.1111/ijpo.12503
|View full text |Cite
|
Sign up to set email alerts
|

Early rapid weight gain among formula‐fed infants: Impact of formula type and maternal feeding styles

Abstract: Summary Background What and how infants are fed are considered important determinants for the risk factor of early rapid gain weight. Objectives We conducted secondary analyses on data from a randomized clinical trial, wherein infants randomized to feed cow milk formula had double the incidence of early rapid weight gain than those fed extensively hydrolyzed protein formula, to determine whether maternal feeding styles had independent effects or interactive effects with infant formula type on early rapid weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…A more recent study evaluating the long-term effects (three and five years of age) of consuming regular versus extensively or partially hydrolyzed formulas during the first year of life showed no differences in growth outcomes [45]. However, two clinical trials conducted by Mennella’s group among infants comparing regular versus hydrolyzed formulas for several months found that those consuming the hydrolyzed formula had a significantly lower weight gain velocity and consumed less to reach satiation than those on the regular formula [46,47,48]. As mentioned earlier, protein in hydrolysate formulas is hydrolyzed and appears to be more easily absorbed; as shown in the aforementioned study, it may exert different satiety responses and, therefore, affect weight gain [20].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study evaluating the long-term effects (three and five years of age) of consuming regular versus extensively or partially hydrolyzed formulas during the first year of life showed no differences in growth outcomes [45]. However, two clinical trials conducted by Mennella’s group among infants comparing regular versus hydrolyzed formulas for several months found that those consuming the hydrolyzed formula had a significantly lower weight gain velocity and consumed less to reach satiation than those on the regular formula [46,47,48]. As mentioned earlier, protein in hydrolysate formulas is hydrolyzed and appears to be more easily absorbed; as shown in the aforementioned study, it may exert different satiety responses and, therefore, affect weight gain [20].…”
Section: Discussionmentioning
confidence: 99%
“…6 As for maternal perception of child weight status, a direct relationship with the success or failure of preventive measures against obesity has been found. 7,11 When mothers correctly perceive their children's weight, they are more likely to choose healthy foods 12 and to delay the introduction of supplementary feeding. 13 It should be noted that most early-age obesity prevention interventions that have so far been analyzed have been carried out after the child's birth and in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…6 Respecto a la percepción materna del peso del hijo, se ha evidenciado una relación directa con el éxito o fracaso de las medidas preventivas contra la obesidad. 7,11 Cuando las madres perciben correctamente el peso de sus hijos, son más propensas a elegir alimentos saludables 12 y a retrasar la introducción de alimentación complementaria. 13 Cabe resaltar que la mayoría de las intervenciones de prevención de obesidad a temprana edad que han sido analizadas hasta el momento, se han efectuado después del nacimiento del niño y en países de ingresos altos.…”
Section: Introductionunclassified